RANCANG BANGUN SISTEM NURSE CALL TERHADAP KEGAGALAN INFUSE PUMP MENGGUNAKAN MIKROKONTROLER ATmega8535 - Heru Heru; Fitria Priyulida (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
The infuse pump is a media device used to provide the patient's body fluids with a certain time and amount. In giving intravenous fluids can have a bad effect on patients. The infusion that is currently used is still manual where errors such as clogging or monitoring of fluids. Therefore, planning an infusion pump that can send notifications when the infusion fluid runs out.In designing this tool aims to design a nurse call on an infusion pump using a microcontroller and sent via Bluetooth to the nurse call. On the Bluetooth call nurse receiving and sending it to the microcontroller will send it to the LCD and the Buzzer sounds if it goes to the input.In this final design using the ATmega8535 microcontroller which will read the incoming data via Bluetooth. LCD and buzzer are used so nurses can see and hear when the infusion fluid runs out.